2018
DOI: 10.1093/jae/ejy009
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Cash Transfer Impacts Through ‘Soft-Conditions’: Evidence from Lesotho†

Abstract: Cash transfer programmes have been shown to have positive effects on a variety of outcomes. While much of the literature focuses on the role of conditionality in achieving desired impact, this paper focuses on the role of 'soft conditionality' implemented through both 'labelling' and 'messaging' in evaluating the impact of the Child Grants Program in Lesotho, an unconditional cash transfer programme targeting poor households with orphans and vulnerable children. Beneficiary households received a clear message … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…We believe the process through which women were encouraged to spend cash on their own nutrition most closely resembles the experience of a cash transfer programme in Lesotho (Pace et al, 2016, 2018) in which complementary labelling and messaging components spurred communities to police beneficiary spending of cash transfers against perceived waste. In our case, NGO staff were motivated to create and enforce spending recommendations for our cash transfers by fears that household members would fail to see their potential value for women's pregnancy and so confiscate them for their own purposes.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…We believe the process through which women were encouraged to spend cash on their own nutrition most closely resembles the experience of a cash transfer programme in Lesotho (Pace et al, 2016, 2018) in which complementary labelling and messaging components spurred communities to police beneficiary spending of cash transfers against perceived waste. In our case, NGO staff were motivated to create and enforce spending recommendations for our cash transfers by fears that household members would fail to see their potential value for women's pregnancy and so confiscate them for their own purposes.…”
Section: Discussionmentioning
confidence: 86%
“…Such constraints can be viewed as a form of ‘soft conditioning’ on transfer use (Pace et al, 2016, 2018; Skovdal et al, 2013). ‘Hard’ conditions refer to formal requirements for continued receipt of cash transfers which are enforced by an external implementing agent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the CGP is unconditional, program messaging did affect child schooling (Pace et al. ). Further, an impact evaluation study carried out by Oxford Policy Management () found that the CGP had a large effect on the proportion of children aged 6–19 who were attending school.…”
Section: Lesotho's Cgpmentioning
confidence: 99%
“…For example, changes in prices could affect household consumption as well as the outcomes of interest (Attanasio et al, 2013). Also, increasing household consumption by a cash transfer could change household's preferences and the additional income could be spent in a different way than current income (Pace et al, 2018). The simulations in this chapter therefore represent a very simplified version of reality.…”
Section: Simulationsmentioning
confidence: 99%